Two Threats to Precision Medicine Equity - Matthew, Dayna Bowen (Ethn Dis, 2019)
In January 2015, President Barack Obama unveiled the “Precision Medicine Initiative,” a nationwide research effort to help bring an effective, preventive, and therapeutic approach to medicine. The purpose of the initiative is to bring a precise understanding of the genetic and environmental determinants of disease into clinical settings across the United States.(1 )The announcement was coupled with $216 million provided in the President’s proposed budget for a million-person national research cohort including public and private partnerships with academic medical centers, researchers, foundations, privacy experts, medical ethicists, and medical product innovators. The Initiative promises to expand the use of precision medicine in cancer research and modernize regulatory approval processes for genome sequencing technologies. In response, Congress passed the 21st Century Cures Act in December 2016, authorizing a total of $1.5 billion over 10 years for the program.(2) Although the Precision Medicine Initiative heralds great promise for the future of disease treatment and eradication, its implementation and development must be carefully guided to ensure that the millions of federal dollars expended will be spent equitably. This commentary discusses two key threats to the Precision Medicine Initiative’s ability to proceed in a manner consistent with the United States Constitutional requirement that the federal government shall not “deny to any person . . . the equal protection of the laws.”(3 )In short, this commentary sounds two cautionary notes, in order to advance precision medicine equity. First, achieving precision medicine equity will require scientists and clinicians to fulfill their intellectual, moral, and indeed legal duty to work against abusive uses of precision medicine science to advance distorted views of racial group variation. Precision medicine scientists must decisively denounce and distinguish this Initiative from the pseudo-science of eugenics – the immoral and deadly pseudo-science that gave racist and nationalist ideologies what Troy Duster called a “halo of legitimacy” during the first half of the 20th century.(4) Second, to combat the social threat to precision medicine, scientists must incorporate a comprehensive, ecological understanding of the fundamental social and environmental determinants of health outcomes in all research. Only then will the Precision Medicine Initiative live up to its potential to improve and indeed transform health care delivery for all patients, regardless of race, color, or national origin.